Marriage and Advance Consent to Sex: A Feminist Judgment in R v JA - Koshan, Jennifer (Oñati Socio-Legal Series, 2016)
This paper is a feminist judgment in R v JA (Supreme Court of Canada 2011), a spousal sexual assault case involving the issue of whether parties can consent in advance to sexual activity that will occur while they are asleep or unconscious. The Supreme Court’s ruling in JA has generated critique and debate amongst feminist and law and sexuality scholars that pits women's equality and security interests against their affirmative sexual autonomy. Using the methodology of a feminist judgment, I endeavour to analyze whether it is possible to adopt an approach to advance consent that protects or at least balances all of these interests. My particular focus is the spousal context, where courts have often interpreted the sexual assault provisions of the Criminal Code to the detriment of women’s sexual integrity and equality, yet where arguments about affirmative sexual autonomy have also predominated. Taking a harm-based approach to criminality that considers both negative and positive sexual autonomy, the judgment concludes that advance consent should not be considered valid without certain legal safeguards being put into place.Este artículo es una sentencia feminista de R v JA (Tribunal Supremo de Canadá 2011), un caso de agresión sexual conyugal que implica la cuestión de si las partes pueden consentir de antemano una actividad sexual que ocurrirá mientras están dormidos o inconscientes. El fallo de la Corte Suprema en JA ha generado críticas y debates entre feministas e investigadores en derecho y sexualidad, que enfrentan los intereses de igualdad y seguridad de la mujer con su autonomía sexual afirmativa. Utilizando la metodología de un juicio feminista, se intenta analizar si es posible adoptar un enfoque de consentimiento anticipado que proteja, o al menos equilibre, todos estos intereses. El enfoque particular es el contexto conyugal, donde los tribunales han interpretado a menudo las disposiciones sobre el asalto sexual del Código Penal en detrimento de la integridad sexual y la igualdad de las mujeres, incluso también donde también han predominado los argumentos sobre la autonomía sexual positiva. A partir de un acercamiento a la criminalidad basado en el daño, que considera la autonomía sexual negativa y positiva, la sentencia concluye que el consentimiento previo no debe ser considerado válido sin que se pongan en práctica ciertas garantías legales. DOWNLOAD THIS PAPER FROM SSRN: https://ssrn.com/abstract=2891024